Efektivitas Distribusi Pupuk Bersubsidi di Desa Wajak, Kecamatan Wajak, Kabupaten Malang - Surono, Anggun Kurniawati; Widayanti, Sri; Sudiyarto, Sudiyarto (Department of Agribusiness, Halu Oleo University, 2021)
This study describes the implementation of subsidized fertilizer distribution in Wajak village and analyzes the effectiveness of subsidized fertilizer distribution in Wajak village. The research location was conducted in Wajak village, Wajak sub-district, Malang regency, from February until March 2021. The data analysis used is four precise indicators (Price, Time, Place, and Amount) with a sample of 50 farmers. The results of this study are an indicator of an effective place in the subsidized fertilizer policy. There are two indicators, namely price, and quantity which are stated to be quite effective. And one indicator is the time which is declared ineffective.